Traveling Behavior Model for Primary School - Waewthaisong, Manascha; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Richtmann Publishing, 2012)
The objective of this research was to develop an environmental traveling behavior model for primary school. Thesimple random sampling was employed to select the sample of 400 students from 5,220 students in Ampur Namsom, UdonthaniProvince. Questionnaire was used as instrument for data collection. Pearson Correlation and Path Analysis will be used for dataanalysis.The results revealed that psychological traits in terms of goal of life (GL) showed directly affected to inspiration of publicconsciousness in aspects of role model (RM) with .532, It also showed directly affected to traveling behavior (TB) and energyconsumption behavior (EB) with .513 and .458. Moreover, psychological states (PS) in terms of religion belief (RB) showeddirectly affected to inspiration of public consciousness in aspects of role model (RM) with .567 and of role model (RM) alsodirectly affected to traveling behavior (TB) and energy consumption behavior (EB) with .601 and .599. Considering onenvironmental education, environmental attitude (AT) showed directly affected to inspiration in aspects of role model (RM) with.575 and it showed also directly affected to inspiration in aspects of impressive environment (IE) with .638 and directly affectedto traveling behavior (TB) and energy consumption behavior (EB) with .574 and 506. Energy consumption behavior (EB) showeddirectly affected to traveling behavior (TB) with .466.